2021
DOI: 10.1021/acs.analchem.1c04460
|View full text |Cite
|
Sign up to set email alerts
|

Sample Preparation for Lab-on-a-Chip Systems in Molecular Diagnosis: A Review

Abstract: Rapid and low-cost molecular analysis is especially required for early and specific diagnostics, quick decision-making, and sparing patients from unnecessary tests and hospitals from extra costs. One way to achieve this objective is through automated molecular diagnostic devices. Thus, sample-to-answer microfluidic devices are emerging with the promise of delivering a complete molecular diagnosis system that includes nucleic acid extraction, amplification, and detection steps in a single device. The biggest is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 83 publications
0
16
0
Order By: Relevance
“…[ 23 ] Therefore, pathogen enrichment and matrix removal are essential for effectively detecting CRISPR‐based microfluidic platforms, particularly for clinical or environmental samples with low pathogen concentrations and complex constituents. [ 24 , 25 ] Although conventional sample pretreatment is implemented in the centralized laboratory, the microfluidic technique represents a simplified alternative, such as employing a filtration step without a centrifuge. Cell lysis to release target analytes is a crucial step that can be integrated into microfluidic devices through thermal, chemical, enzymatic, mechanical, and electrical treatments, according to the acquired quality of extraction and sample type.…”
Section: Sample Preparationmentioning
confidence: 99%
“…[ 23 ] Therefore, pathogen enrichment and matrix removal are essential for effectively detecting CRISPR‐based microfluidic platforms, particularly for clinical or environmental samples with low pathogen concentrations and complex constituents. [ 24 , 25 ] Although conventional sample pretreatment is implemented in the centralized laboratory, the microfluidic technique represents a simplified alternative, such as employing a filtration step without a centrifuge. Cell lysis to release target analytes is a crucial step that can be integrated into microfluidic devices through thermal, chemical, enzymatic, mechanical, and electrical treatments, according to the acquired quality of extraction and sample type.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Wicking is a ubiquitous dynamic wetting process in which capillary force drives liquid flow in porous systems. , With the development of high technology, such as thermal management materials, lab-on-a-chip , and electronic devices, , the complex and diverse application environment also puts more demands on the innovation of technology. Since wicking possesses miniaturization ability, simple equipment, and does not require external energy supply, it has been widely utilized in phase change boiling heat transfer, water harvesting in arid environments, , moisture wicking wearable equipment, micro biochemical testing platforms, and microfluid manipulation equipment. , In particular, wicking phenomena have become the hot direction of microfluidic manipulation technology development, such as precise one-dimensional fluid manipulation, two-dimensional planes for fluid collection, and dynamic liquid filling and mixing .…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidics deals with the control and manipulation of fluids on a sub-millimeter scale in a single or network of microchannels [ 1 , 2 , 3 , 4 , 5 ]. With the development of technology, microfluidics is becoming a part of the complex miniaturized systems called Lab-on-a-Chip (LOC) [ 6 , 7 , 8 ] that contain multiple operations integrated into one single chip, such as reagent mixing [ 9 ], particle separation [ 10 ], DNA extraction and amplification [ 11 ], detection [ 12 ], etc. Recent studies demonstrate that LOC systems had found application in various point-of-care analyses such as the detection of foodborne pathogenic bacteria in food quality control [ 13 , 14 , 15 ], environmental monitoring [ 16 , 17 ], and biomarker detection [ 18 , 19 ], or could be used for developing an organ-on-chip for in vitro analysis [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%